Examination of the Nature Conservation Aspects of Agroecology Based on the Practices of Farmers and Opinion of Consumers - Harkányi, Annamária; Ujj, Apolka (JOURNAL OF LANDSCAPE ECOLOGY, 2023)
In recent decades, the practices of agricultural production and the food system have changed radically. Improper and unsustainable agricultural practices have led to one of the most pressing environmental problems of our time, which affects our whole society as well. However, there are environmentally friendly and economically sustainable long-term farming forms and alternative approaches. Agroecology supports the transition to a fair food system not only with a scientific approach, but also from a social and practical point of view. The Food and Agriculture Organization of the United Nations (FAO) has developed 10 basic elements of agroecology, which help in creating a sustainable, ’restorative’ farming system. Of the 10 elements, 4 are related to nature conservation, that were selected for our research. These are the following: biodiversity, synergies, recycling and resilient resilience. In order to examine the selected elements, both the farmer’s and the consumer’s sides were analysed. Accordingly, for inspecting the farmer side, an in-depth interview was prepared and conducted with the managers of the two examined farms, while on the consumer side, a questionnaire survey was applied among the farms’ regular customers. To compile the questions, we defined indicators based on relevant literature, to which interview/questionnaire questions were assigned. The results of the in-depth interviews described the practices the two investigated farms apply while following the elements of agroecology related to nature conservation. Based on the consumer questionnaire, it can be concluded that buyers are characterised by awareness, and their decisions are not only influenced by the need for healthy food, but also by the farms’ environmentally friendly and sustainable agricultural practices.